PEMBELAJARAN SPEAKING DENGAN TEKNIK IMITASI MAHASISWA JURUSAN PGSD SEMESTER GANJIL UNIVERSITAS TRILOGI JAKARTA - Oktariyani Oktariyani (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2020)
Speaking learning with Imitation technique is an action in imitating words or sentences that are appropriate to the native speaker. This imitation technique consists of the stages of listening and reading, listen and imitate, and time to shadow. The purpose of this learning technique is to know how effective this technique is in improving students' speaking skills in the PGSD University Trilogy Department. The method used in this study is descriptive qualitative. Analysis of research data was carried out in three ways, namely data reduction, data presentation, drawing conclusions and verification. The results showed that the research subjects experienced difficulties in the process of speaking with imitation techniques, namely at the read and imitate stage there were 15 students and the time to shadow stage there were 28 students.